Experimental assessment of well integrity for CO2 geological storage: A numerical study of the geochemical interactions between a CO2-brine mixture and a sandstone-cement-steel sample. (March 2017) - Tremosa, Joachim; Mito, Saeko; Audigane, Pascal; Xue, Ziqiu
Abstract: Geologic storage of CO2 is one option for avoiding CO2 emissions from a large-scale point source such as a thermal power plant and a gas refinery. The alteration of well materials by CO2 under reservoir conditions requires characterization because the wells are the main possible leakage pathways for CO2 from a geological reservoir. This paper presents a numerical modeling of interaction experiments involving a composite well sample formed from steel casing surrounded by Portland cement, itself surrounded by sandstone and CO2 -saturated brine at 10 MPa and 50 °C during a period of up to 8 weeks, as reported by Mito et al. (2015). A reactive-transport model was developed to simulate diffusion of the CO2 -saturated brine in the well sample and the resulting successive dissolution/precipitation reactions in the sandstone, cement and steel. The observed changes in mineralogy (which primarily consist of dissolution of portlandite and Ca-rich CSH phases and precipitation of calcite, amorphous silica and zeolite) and the associated evolution in brine composition were reproduced by the model. A buffering role of sandstone on the cement degradation was evidenced, thus avoiding the re-dissolution of calcite usually observed in experiments with direct interaction between cement and CO2 -saturated brine. Interestingly, the model results also noted a possible perturbation in the measured pH and Ca content due to CO2 outgassing during solution sampling. The Si behavior control linked with the uncertainty in zeolite stability is also discussed. Highlights: Experiments on the interactions among CO2, brine, cement, sandstone and steel were modeled. The cement alteration and carbonation reactive pathway were reproduced. The pore space of the sandstone-buffered cement underwent degradation. The model can be used in well integrity predictions under storage conditions.